Assessment of the right Metered Dose Inhaler (MDI) technique patient with asthma and chronic obstructive disease (COPD) at Hospital Sultanah Nurzahirah K. Terengganu / Mohd Azmie Endut and Muhammad Adib Omar - Endut, Mohd Azmie; Omar, Muhammad Adib (2009)
Asthma is a one of the respiratory diseases. Metered Dose Inhaler (MDI) is one of the types of inhaler that use in asthma therapy. MDI can divide into two type relievers and preventers. Using such an MDI requires considerable coordination, and it is important technique. It is the dose may not to be inhaled correctly. This not only makes it less effectively. There are nine steps of effective MDI technique. Those steps can be further divided into common step and essential step. Please refer to appendix 14 and 15 to learn more about common and essential step. The main objective is to determine the correct technique in asthmatic or COPD patients using MDI in Respiratory Clinic at Hospital Sultanah Nur Zahirah Kuala Terengganu. Beside that, to determine patients awareness to maintean their MDI. Furthermore, we recommended the right technique using MDI that can improve patient health and the last one is to determine the factors that contribute to inappropriate at inhalation technique. For the result we focus about inhalation technique that done by patients. From the nine given steps, we gave mark to patients to evaluate their skill of how to use their MDI appropriately. A total of 33 patients (47%) achieved unsatisfactory mark, 7 patients (10%) received satisfactory score while the remaining 30 patients (43%) obtained good mark. This data show that the patients who gained unsatisfactory mark almost equivalent with the patients who got satisfactory score. Thus, there still some weaknesses performed by the patients when applying MDI. The data was collected by questionnaires that were distributed to 70 asthmatic or COPD patients at respiratory clinic that using MDI from June to July 2009.We use Microsoft office excel 2007 to analyze all data that we collected. Form this study we can conclude that many asthmatic or COPD patients from Respiratory Clinic at Hospital Sultanah Nur Zahirah Kuala Terengganu do not comply with the right technique using MDI properly.